Italian Fascisms Soviet Enemy and the Propaganda of Hate, 1941-1943 - Marla Stone (Journal of Hate Studies, 2012)
In conjunction with the war against the Soviet Union which began in June 1941, the Italian Fascist regime promulgated a virulent brand of anti-communism and oversaw a campaign of hate-mongering propaganda targeted at its Soviet enemy. This propaganda produced to justify the war highlighted the Manichean struggle against the Soviet Union and the special horrors of the Soviet communist enemy. Using longstanding stereotypes about a Russian lack of civilization, 19th-century ideas about racially expressed biological difference, and more recent tropes about Bolshevik barbarism and immorality, official representations of Fascisms historic enemythe communistput forward a racially degenerate, godless peril from the East bent on the destruction of Western civilization and on the desecration of the Italian family and the Catholic faith.